If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + 3y = 3 Solving 16x + 3y = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 16x + 3y + -3y = 3 + -3y Combine like terms: 3y + -3y = 0 16x + 0 = 3 + -3y 16x = 3 + -3y Divide each side by '16'. x = 0.1875 + -0.1875y Simplifying x = 0.1875 + -0.1875y
| .25x=866 | | -6=5(x+3)-6x | | -6=(x+3)+6x | | .33x=.25x | | -6=(x+3)+4x | | c^2-7c-12=0 | | c^2-35-60=0 | | 11x=64+36 | | 2x-3+2x-3=1 | | 5c^2-35c=60 | | 9x=56+2x | | x^4-4*x^3=0 | | x=2x+8 | | x^2-8xy+16y^2-25=0 | | 12p=12p+4 | | u^2+49=2u^2-6u+64 | | p-4=p+p | | (7x)(3x^9u^6)(2u^4)= | | 2x+3=36x | | x^3-x^2=0 | | s^2-7x-8=0 | | 4y+3y=(2)+4y | | 9a^4-a^2b^2=0 | | 8s^2-2x-3=0 | | x^2-5x-6=3 | | 4s^2+s=3 | | 4y+3+y=(y+2)+4 | | 4s^2+9x-9=0 | | s^2-6x-7=0 | | x^2-12x=-7 | | 2s^2+5s+2=0 | | s^2-9s+14=0 |